1994
DOI: 10.1590/s0037-86821994000400007
|View full text |Cite
|
Sign up to set email alerts
|

Associação de cromoblastomicose e hanseníase: relato de dois casos

Abstract: Ao estudar 30 casos de cromoblastomicose diagnosticados no Hospital dos Servidores doEstado do Maranhão, no período de novembro de 1988 a março de 1993, os autores observaram 2 (6,6 %) casos, que apresentaram associação desta doença com hanseníase. O prim eiro paciente desenvolveu as duas doenças concomitantemente, apresentando espessamento no nervo cubital bilateral, malperfurante plantar em p é direito e lesões em placas verrucóides na perna esquerda, com biópsia de nervo cubital direito positiva p a ra hans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…There are few reports of this coinfection, most of them from Brazil. 7 , 17 , 46 , 50 , 77 , 78 , 79 , 80 , 81 Two of the patients reported in this research were elderly (65 years or older), coinciding with two previous reports. 77 , 79 The explanation for the occurrence of chromoblastomycosis‐leprosy coinfection in the elderly can be very complex and could be related to immunosenescence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There are few reports of this coinfection, most of them from Brazil. 7 , 17 , 46 , 50 , 77 , 78 , 79 , 80 , 81 Two of the patients reported in this research were elderly (65 years or older), coinciding with two previous reports. 77 , 79 The explanation for the occurrence of chromoblastomycosis‐leprosy coinfection in the elderly can be very complex and could be related to immunosenescence.…”
Section: Discussionsupporting
confidence: 90%
“…Three patients had chromoblastomycosis‐leprosy coinfection. There are few reports of this coinfection, most of them from Brazil 7,17,46,50,77–81 . Two of the patients reported in this research were elderly (65 years or older), coinciding with two previous reports 77,79 .…”
Section: Discussionsupporting
confidence: 89%
“…In the present casuistic we found only two cases of the disease in immunosuppressed hosts, including one case each of renal transplantation and systemic lupus. Other authors have also reported few cases of CBM in patients undergoing solid organ transplantation (kidney, heart and liver), pemphigus vulgaris, rheumatologic diseases (lupus erythematosus), solid tumors and chronic steroid users (type 2 leprosy reaction) [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Facial lesions may produce eyelid retraction, leading to several grades of ectropion, xerophthalmia, and keratitis. Associations of CBM with several infectious diseases have been reported, including osteomyelitis, paracoccidioidomycosis, leishmaniasis, and leprosy (126,(250)(251)(252)(253)(254). These coinfections may increase the progression of both diseases, resulting in prolonged antifungal therapy and increased toxicity related to the respective therapies.…”
Section: Complications and Sequelaementioning
confidence: 99%